Peran Bahasa Indonesia Dalam Proses Ekonomi di Tempat Wisata Shava Beach Resort, Kecamatan Kabila, Kabupaten Bone Bolango, Gorontalo - Dali, Meilina Widya; Monoarfa, Fidyawati; Uuju, Uuju; Paputungan, Diva Agista; Rasyid, Inayah Triwahyuni; Rajak, Sri Fransiska N; Sahrul, Sahrul; Kinga, Natasya Aulia; Daud, Regina Putri; Apriliya, Yusra; Lengkas, Alya Syabrina; Doe, Fikran H; Rivai, Putri Denada; Yusuf, Fatmawati; Abas, Mohammad Jibril Ashil (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Indonesian is the official language of the country which has an important role in supporting economic processes, particularly in the tourism sector. This study aims to identify the role of the Indonesian language in interactions between managers and visitors at Shava Beach Resort, located in Kabila District, Bone Bolango Regency, Gorontalo. The research employed a descriptive method with a qualitative approach. Data collection techniques included observation, interviews, and documentation. The results show that Indonesian functions not only as a means of communication but also as a medium for learning as well as an effective and communicative promotional tool. The use of Indonesian in conveying information and providing services enhances the quality of tourists' experiences and strengthens the brand image of the tourist destination. Therefore, the Indonesian language plays an important role in the development of the tourism economic process in this region.